Effectiveness of the interventions in preventing the progression of pre-frailty and frailty in older adults: a systematic review protocol. - Apóstolo, João Luís Alves (2016)
The objective of this review is to identify the effectiveness of the interventions in preventing progression of pre-frailty and frailty in older adults. More specifically, the review questions are: What is the effectiveness of interventions in preventing or reducing frailty in older adults? How does effectiveness vary with degree of frailty? Are there factors that influence the effectiveness of interventions? What is the economic feasibility of interventions for pre-frailty and frailty?